CEGAH COVID-19 DENGAN MEMBAGIKAN MASKER DAN PENYULUHAN KE MASYARAKAT KOTA BATAM - Simamora, Helprida; Yopi; Sihombing, Jonmaianto (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2025)
Abstract The COVID-19 pandemic has had a major impact on people's health and social activities, especially in urban areas with high mobility such as Batam City. The low awareness of some people about health protocols and limited access to personal protective equipment are challenges in efforts to prevent the spread of the virus. This community service activity aims to increase awareness and healthy living behavior through the distribution of masks and counseling on COVID-19 prevention. The implementation method is carried out through an educational and participatory approach, including socialization of health protocols, demonstrations of the correct use of masks, and distribution of masks to the public in public areas. The results of the activity show that there is an increase in public understanding of the importance of using masks and implementing health protocols in daily life. The enthusiasm of the community during the activity showed that direct education and the provision of prevention facilities were effective strategies in supporting the control of the spread of COVID-19. This activity is expected to contribute to building the collective awareness of the people of Batam City to maintain their health and the environment.